2001
DOI: 10.1088/1126-6708/2001/02/005
|View full text |Cite
|
Sign up to set email alerts
|

Phase structure of the 5D abelian Higgs model with anisotropic couplings

Abstract: We establish the phase diagram of the five-dimensional anisotropic Abelian Higgs model by mean field techniques and Monte Carlo simulations. The anisotropy is encoded in the gauge couplings as well as in the Higgs couplings. In addition to the usual bulk phases (confining, Coulomb and Higgs) we find four-dimensional "layered" phases (3-branes) at weak gauge coupling, where the layers may be in either the Coulomb or the Higgs phase, while the transverse directions are confining. *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…We fix β h ′ = 0.001 and β R , β g and vary β h and β g ′ . For β g = 4 (weak 4d gauge coupling) [5] we find the following "snapshot" cf. fig.…”
Section: The Modelmentioning
confidence: 92%
See 1 more Smart Citation
“…We fix β h ′ = 0.001 and β R , β g and vary β h and β g ′ . For β g = 4 (weak 4d gauge coupling) [5] we find the following "snapshot" cf. fig.…”
Section: The Modelmentioning
confidence: 92%
“…In the past year we have studied what happens, when scalar fields are included [5,6]. We have found that an additional "layered" phase appears.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we move along the line ¼ 1:10, in order to study the layer-Coulomb phase transition at finite temperature. 8 As we will explain in Sec. IV B and using the Figs.…”
Section: Study Of the Phase Diagram For L T ¼mentioning
confidence: 99%
“…We start with the action (1). We fix the gauge by imposing U4(x) = I and use the translation-invariant Ansatz [1,2,7], Uμ(x) = v, 1 ≤ µ ≤ 3; U5(x) = v . We also introduce the variables for the Higgs field,…”
Section: Mean Field Approachmentioning
confidence: 99%
“…This work is a second, more comprehensive, view of the possibility of taking a layered phase of a higher dimensional U(1)-Higgs model which originated in [7]. Since the couplings in the five-dimensional theory have dimensions the theory needs cut-off and it should be defined in a strongly coupled phase.…”
Section: Introductionmentioning
confidence: 99%